Medial Tibial Osteophyte Width Strongly Reflects Medial Meniscus Extrusion Distance and Medial Joint Space Width Moderately Reflects Cartilage Thickness in Knee Radiographs - Sekiya, Ichiro; Sasaki, Sho; Miura, Yugo; Aoki, Hayato; Katano, Hisako; Okanouchi, Noriya; Tomita, Makoto; Masumoto, Jun; Koga, Hideyuki; Ozeki, Nobutake (Journal of magnetic resonance imaging, 2022)
Background The presence of medial tibial osteophytes on knee radiographs suggests cartilage wear, but may be associated with medial meniscus extrusion (MME). The joint space width of the medial compartment consists anatomically of cartilage and the medial meniscus, but which is most responsible for joint space narrowing remains unclear. Magnetic resonance imaging (MRI) reveals MME and cartilage thickness. Purposes To determine which radiographic medial tibial osteophyte width correlates better with cartilage thickness or MME distance and which radiographic medial joint space width correlates better with cartilage thickness or MME distance. Study Type Cross‐sectional. Population Total of 527 subjects, 253 females and 274 males, aged 30–79 years, included in the Kanagawa Knee Study. Field Strength/Sequence 3 T/fat‐suppressed spoiled gradient echo and proton density weighted. Assessment The medial tibial osteophyte width and “the minimum joint space width at the medial compartment” (mJSW) were measured from plain radiographs. The cartilage region was automatically extracted from MRI data using software. The medial femoral and tibial cartilage regions were each divided into nine subregions, and the average thickness of the cartilage was determined in each region and subregion. MME was manually measured by two orthopedic surgeons using MRI coronal section images. Statistical Tests Pearson's correlation coefficient and their comparison, with P < 0.05 considered statistically significant. Results The absolute values of the correlation coefficients were 0.33 at maximum between osteophyte width and cartilage thickness and 0.76 between osteophyte width and MME; the value was significantly higher with MME than with cartilage thickness (P < 0.001). The absolute values of the correlation coefficients were 0.50 at maximum between mJSW and cartilage thickness and 0.16 between mJSW and MME; the value was significantly higher with cartilage thickness than with MME (P < 0.001). Data Conclusion The medial tibial osteophyte width strongly reflected MME and the medial joint space width moderately reflected cartilage thickness. Level of Evidence 3 Technical Efficacy Stage 3